Consumption awareness of Indian community towards food label in Klang, Selangor - Zul Ariff Abdul Latiff; Mohammad Amizi Ayob (2015)
As the third largest ethnic in Malaysia, Indian community plays an important role in the increasing economy of food products and their awareness towards food labels can be considered as important indicator too. The Theory of Planned Behavior (TPB) is utilized as a theoretical framework in explaining the Indian consumers’ awareness in consuming food products with the food labels in Klang, Selangor, Malaysia. Primary data was obtained through the designated questionnaire which had been distributed to 300 respondents representing Indian consumers. The data was obtained using stratified random sampling technique. The study used descriptive analysis, chi-square test, and reliability test in order to analyze the collected data. The overall results indicate that the presence of food labels have significance relationship with the awareness of Indian consumers in buying and consuming the food products. Besides, most of the respondents concerned about religious and healthy practices. Thus, this study has become a strong indicator on how the awareness level of Indian consumers towards food label.